Is refinancing solely motivated by misappropriation? - Chun Liu; Liang Sun (China Journal of Accounting Research, 2012)
Misappropriation has become the accepted explanation for the refinancing behavior of Chinese listed companies, although the evidence in support of such an explanation is worthy of further discussion. We argue that if a planned refinancing exercise does not become a reality, post-refinancing performance depends on the initial motivation for refinancing, i.e. misappropriation or the maximization of firm value. The success and failure samples provided by the approval system of the Chinese securities market provide us with a natural laboratory in which to distinguish between these two possible motivations for the refinancing behavior of Chinese listed firms. The results show the post-refinancing performance of firms in the success sample to be significantly better than the performance in the failure sample, with the difference even more significant when larger agency costs or more financial constraints exist. These findings indicate that Chinese listed companies do not engage in refinancing for misappropriation purposes alone. Rather, refinancing is more likely to be a rational choice made in full consideration of the costs and benefits. This paper provides new ideas for reexamining the motivations for the refinancing behavior of China's listed firms. It also has one major policy implication. That is, relaxing and/or simplifying the country's refinancing regulations could help to improve the efficiency of resource allocation in the Chinese securities market.
Keywords: G30; G32; G38; 650; Refinancing; Misappropriation